KAJIAN KRITIS FAIRCLOUGH DALAM ULTIMATUM KAPOLRI TITO ATAS SIKAP EKO PATRIO MENGENAI KASUS BOM PANCI - Ayu, Rizka Kurnia (Faculty of Humanities, Diponegoro University, 2017)
Discourses that appear in text and conversation are not neutral. It is a form of subjectivity that leads to power struggles. Such as the discourse of â€œBomb Panâ€ as the diversion issues on the Ahok casewhich was heralded by Eko Patrio, which was then responded by the Chief of Police Tito who was in charge of handling the bomb pan case together Densus 88.Police Chief against Eko delivered in ultimatum form that finally made Eko doing a series of strange such as transforming himself from a suspect to a victim of online media libel. Changes in Eko's attitude due to Tito's ultimatum made the researcher interested in analyzing the contents of the Ultimatum. Through Fairclough's critical discourse (textual analysis, discursive practice, and social praxis) it was found that the Chief of Tito's decree using the modalities of service negotiation to generate symbolic power over its performance as a police chief can not be doubted and must be obeyed by anyone including political institutions